(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Air pollution generates serious respiratory and cardiac diseases which may be deadly. Children are most typically afflicted, resulting in pneumonia or respiratory issues, including asthma. Acids rain, degradation of the ozone layer, as well as global warming are among the detrimental repercussions. air pollution is described as the introduction of toxic or otherwise hazardous chemicals into the air. These substances might vary from poisonous chemicals to biological molecules, but they all represent a danger to human and environmental health in one way or another. As you may guess, pollution affects overall pollution levels, which may have substantial, detrimental consequences on both people and animals alike. High air pollution concentrations might result in eye discomfort, skin rashes, respiratory difficulties, heart illness, and even early mortality in humans. Animals may display comparable symptoms with much more severe indicators, particularly when one of their sources of food is directly poisoned. In this paper, the author talks about air pollution and its future challenges. The main objective of this paper is to understand about Present and Future Challenges of Air Pollution. In the future, this paper helps to learn more about air pollution or its future challenges.